2020
DOI: 10.1177/0264619620972154
|View full text |Cite
|
Sign up to set email alerts
|

The certification of vision impairment: A regional 21st century perspective

Abstract: Certification and registration of those who are sight impaired (SI) provides commissioners, and the providers of health and social care support to those with vision loss, with quantifiable data on the extent of blindness and sight impairment within a community. In this article, we outline the results of a comprehensive review of certification/registration pathways and processes in Northern Ireland and highlight achievements to date. The Developing Eyecare Partnership (DEP) CVI Task Group established by the Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Previous annual certification reports showed that Northern Ireland has lower certification rates that the rest of the United Kingdom (Canavan et al, 1997). The Northern Ireland Developing Eyecare Partnership developed a plan in 2014 to improve certification rates in Northern Ireland (Jackson et al, 2020). In 2017, all certification processes and pathways were reviewed and improved (Jackson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous annual certification reports showed that Northern Ireland has lower certification rates that the rest of the United Kingdom (Canavan et al, 1997). The Northern Ireland Developing Eyecare Partnership developed a plan in 2014 to improve certification rates in Northern Ireland (Jackson et al, 2020). In 2017, all certification processes and pathways were reviewed and improved (Jackson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The Northern Ireland Developing Eyecare Partnership developed a plan in 2014 to improve certification rates in Northern Ireland (Jackson et al, 2020). In 2017, all certification processes and pathways were reviewed and improved (Jackson et al, 2020). Educational activities were undertaken in parallel to promote the new certification pathway to increase the understanding of, and compliance with, the process at both secondary care and community level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations